Evaluating the effectiveness of a physical activity social media advertising campaign using Facebook, Facebook Messenger, and Instagram. Issue 3 (23rd January 2021) - Northcott, Celine; Curtis, Rachel; Bogomolova, Svetlana; Olds, Timothy; Vandelanotte, Corneel; Plotnikoff, Ronald; Maher, Carol
Abstract: Technology-based physical activity programs are a novel solution to the major public health issue of physical inactivity. However, to be successful, there must be a large and population-appropriate uptake, which depends heavily on promotion. This study evaluates the effectiveness of an advertising campaign to disseminate a physical activity smartphone app. The experiment used a 3 × 3 × 3 full-factorial design, examining platforms (Facebook; Facebook Messenger; Instagram), selling-techniques (hard-sell—sending viewers directly to (a) Apple Store or (b) Google Play, and soft-sell—sending viewers from an ad to a (c) landing-page, then to an app store) and themes (Health and Wellbeing; Body and Self-Confidence; Social Enjoyment). Outcomes were reach, click-through, and app downloads. Advertisements reached 1, 373, 273 people, achieving 2, 989 clicks and 667 downloads. Instagram and Facebook Messenger had higher reach compared to Facebook ( F [2, 27] = 27.17, p < .001), whilst Facebook and Facebook Messenger both produced higher click-through ( F [2, 27] = 8.98, p < .001) and downloads ( F [2, 27] = 4.649, p = .018). Selling-technique differed, with soft-selling ads producing greater reach ( F [2, 27] = 4, 616.077, p < .001); however, both hard-selling ads (Apple Store and Google Play) had greater click-through ( F [2, 27] = 10.77, p < .001) and downloads ( F [2, 27] = 3.791, p < .001). Advertising theme varied, with Social Enjoyment themes producing less click-through ( F [2, 27] = 5.709, p = .009) and downloads ( F [2, 27] = 5.480, p = .010). We recommend future studies to consider Facebook and Facebook Messenger, using hard-selling techniques, with themes relating to Health and Wellbeing and Body and Self-Confidence. Abstract : Advertisements targeting women, promoting a health-related physical activity smartphone app, performed better on Facebook and Messenger, using hard-selling techniques, with themes relating to Health & Wellbeing and Body & Self-Confidence."